R&D of Photovoltaic Thermal (PVT) Systems: an Overview - Ahmad Fudholi; Kamaruzzaman Sopian (Institute of Advanced Engineering and Science, 2018)
Photovoltaic thermal (PVT), which is the popular technology for harvesting solar energy, receive solar energy and convert it into electrical and thermal energy simultaneously. In this review, design, heat transfer, energy modelling and performance analysis of PVT systems are presented. Four types of PVT systems base on heat transfer medium; air-based PVT system, water-based PVT system, the combination of water/air-based PVT system, and nanofluid-based PVT system are presented. In addition, major finding on energy and exergy analysis of PVT systems are summarized.